PERBANDINGAN FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PADA BANK PEMBANGUNAN DAERAH DAN BANK-BANK UMUM YANG TERDAFTAR DI BEI - , Rifky Adhitya ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is motivated by the argument that banking is the core system of state finances. Therefore, every bank in Indonesia must have a good performance. Performance indicators can be measured by Return on Assets (ROA) and Return on Equity (ROE). To can assess these indicators, factors such as capital, liquidity, and rentability can be used. These factors could be represented by Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Expense to Operating Income Ratio, and Non Performing Loan (NPL). This research also will assess whether the factors that could influece the bankâs performance will be different or not for each bank. Type of bank that will be used at this research are regional development bank and go public bank. The results of this research are ROA is positively influenced by CAR and LDR and thereâs no independent variables that positively influence ROE. This study also obtain the result that there are differences in the influence of independent variables for ROA and ROE of regional development bank and go public bank. ROA of regional development bank is positively influenced by CAR, LDR, and NPL, while ROA of go public bank is potively influenced by LDR and NPL. Thereâs no independent variables that positively influence ROE of regional development bank while ROE of go public bank is positively influenced by NPL.